Factors of Online Learning Problems During the COVID-19 Pandemic - Sarumpaet, Nur Fitri (Maliki Interdisciplinary Journal, 2024)
The occurrence of a pandemic in 2019 had quite a big impact on all countries in this part of the world and from various aspects of life. One of them is in the aspect of education, where all teaching and learning processes that were originally carried out conventionally have turned online and can be accessed from home. The process of teaching and learning with different methods is certainly inseparable from the various challenges faced by each individual who participates in it. Various aspects such as internet connection, insufficient use of technology, and constraints on disturbance from the surrounding environment are reasons for the inefficient and effective online learning process. This is what needs to be studied further how this aspect influences the factors that influence problems in online learning during COVID-19. The method used in this article is to use a literature study analysis by collecting various articles related to the topic raised so as to be able to provide more in-depth information to the reader. The results of the literature study that has been carried out show that there are several factors that have a very high influence on the online learning process, including technological barriers such as limited internet access, and the use of cell phones or other electronic media that is less supportive, lack of focus during learning takes place, constraints finances, to the number of tasks given.